Potential therapeutic effects of autologous platelet rich plasma on impaired wound healing: a prospective clinical study - Upadhyay, Sachin; Varma, Hashmukh Shantilal; Yadav, Sumit (International Journal of Research in Orthopaedics, 2018)
Background: The evolving state of technology in field of medicine has led to a plethora of new options in the realm of wound healing. The primary objective of present study was to assess the potential therapeutic effects of autologous platelet rich plasma in the healing of wound. Methods: A prospective clinical nonrandomized cohort study was performed in 50 patients (40 males, 10 females) with recalcitrant, chronic; non-healing wounds of different etiologies. Age ranged from 25 to 70 years (mean 39.14±13.38). Eligible patients were treated with autologous platelet rich plasma (PRP) at 4-days intervals for a maximum of 14 sessions. Patients were evaluated (reduction in size of the wound (area)) every week and continued until final healing has achieved. The primary outcome was positive response to therapy, defined as complete healing of the wound and absence of any raw area. Significance was set at p<0.05. Results: The mean time duration to wound healing was 6.33 weeks (S.D±2.16). A statistically significant difference (p<0.05) was observed between the baseline parameters and mean area after PRP injection. After 7 sessions (28 days of therapy) the wounds showed the significant change in wound surface area (p<0.05). None of the patients developed deep or superficial wound infections. Conclusions: There is considerable improvement in wound characteristics like healthy granulation tissue, healing edge, pain, slough, bleeding on touch and discharge after 7 days of PRP therapy and considerable improvement on follow up.